Personal failure (Journal of Parents and Teachers, 2026)
The experience of a parenting school in Madrid is described, which analysed personal failure as a central theme for rethinking the lives and education of children. It proposes a 12-step programme for understanding the feelings that accompany the feeling of failure.
Keywords: Learning; Self-improvement; Personal failure; Prevention